New Private Infrastructure Projects in Developing Countries Continue to Take Place But Projects are Being Affected by the Financial Crisis - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Throughout the financial crisis, new private activity has continued to take place in developing countries with projects being tendered and brought to financial closure. In the first months of the full-scale of the financial crisis (Aug-Nov 2008), the rate of project closure was 26 percent lower than in the same period in 2007. However, since then private activity recovered and the project closure rate in Aug-Dec 2008 was just 15 percent lower than in the same period in the previous year. The slowdown reflects an initial impact of the financial crisis which has made financing (both debt and equity) more onerous and difficult to secure. Infrastructure projects are facing higher cost of financing, and lower demand for infrastructure services is beginning to impact some sectors. The major impact to date is projects being delayed, and, to a lesser extent, cancelled. Transport and energy are the worst affected sectors so far, while Europe and Central Asia (ECA) and upper middle income countries are the most affected groups of countries. It is too early to assess the full impact of the crisis on new Public Private Infrastructure (PPI) projects. Financial markets remain volatile while the financial crisis has now turned into a global economic crisis. As the 'flight to quality' sets in for banks and other financiers, the likely impact will be more stringent financial conditions, not only via higher cost of financing but also with lower debt/equity ratios, reduced maturities and more conservative risk allocation structures.